The Collapse of Trust: Negotiating Amanah and Digital Sovereignty in Indonesia’s Sacred Data Regime - Ramadhan, Hassin Dzikry (Journal of Islamic Philosophy and Contemporary Thought, 2025)
The 2024 cyber crisis at Indonesia’s National Data Center exposed more than a technical malfunction—it revealed a moral rupture in the state’s handling of citizens’ sensitive information. Public debate largely revolved around infrastructure and economic losses, leaving unaddressed the ethical fragility surrounding what this study terms sacred data: information about religious identities, practices, and communal networks consolidated by the state. Using Critical Discourse Analysis (CDA) and a relational ethics framework rooted in the Islamic notion of amanah, the article examines how technocratic governance has marginalized moral responsibility and silenced affected communities. Findings reveal that the incident gave rise to three interconnected risks: individual discrimination, erosion of communal autonomy through digital profiling, and geopolitical exposure, ultimately leading to data colonialism. These vulnerabilities point to a deeper failure of moral imagination—a crisis of amanah in the digital realm. The article argues that data must be reenvisioned as a sacred trust that links the state, society, and the divine. It concludes by calling for a transformation of Indonesia’s data governance toward an amanah-based ethics that restores moral agency, ensures digital sovereignty, and redefines the social contract between citizens and the state in the age of technocratic power.